Pengaruh Kompensasi dan Disiplin Kerja Terhadap Kinerja Karyawan di PT Aisin Indonesia Automotive: Studi pada Karyawan di Plant Body PT Aisin Indonesia Automotive - Supriyanto; Wanta; Asep Darojatul Ramli (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
Human resources play an important role in the complex scope of employment, the principles of welfare and justice and effectiveness in carrying out work are priorities in carrying out company operations. Compensation provided by the company is often a factor in whether employee performance is good or bad, as well as work discipline which is the basis for carrying out work according to standard operating procedures. The study carried out has the aim of being able to find out, analyze and explain the influence of work discipline and compensation on employee performance at PT Aisin Indonesia Automotive (study of employees at the PT Aisin Indonesia Automotive plant body). The method in this study uses a quantitative model with a descriptive verification approach technique. For this study, the population recorded included all Plant Body employees of PT Aisin Indonesia Automotive. The sample used in this study was 130 respondents with the sampling technique used, including non-probability sampling using a sampling technique, namely saturated sampling (census). Data analysis in this study used path analysis assisted by the IBM SPSS V 29.0 analysis tool. The research results show that the work discipline variable has a significant partial influence on employee performance variables. The compensation variable has a significant partial influence on the employee performance variable. And there is a significant simultaneous influence between compensation variables and work discipline on employee performance at PT Aisin Indonesia Automotive .